Research Progress in the Treatment of Idiopathic Membranous Nephropathy with Traditional Chinese Medicine - Yan, Kejia; Chen, Xinzheng (Journal of Contemporary Medical Practice, 2025)
Idiopathic membranous nephropathy (IMN) is an autoimmune disease and is the main cause of nephrotic syndrome. At present, there are many controversies about the means and effect of clinical treatment of IMN. Combined with cyclophosphamide and hormone, as the first-line treatment regimen for IMN, have obvious toxic and side effects, while calcineurin inhibitor, as the initial alternative treatment regimen, although it can effectively improve the clinical manifestations of IMN proteinuria and so on,it has ahigh degree of nephrotoxicity. In recent years, the TCM treatment of IMN has made great clinical achievements. TCM treatment follows the principle of “overall concept, syndrome differentiation and treatment”, and adopts the characteristic therapy of internal and external treatment, which can effectively alleviate the refractory symptoms of IMN and has a good application prospect. To this end, this paper collected the literature data related to TCM treatment of IMN in recent years, and summarized the etiology and pathogenesis of IMN and TCM treatment of IMN, in order to provide a reliable basis for TCM treatment of IMN.